1989
DOI: 10.1246/bcsj.62.1032
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of α,ω-Type Surfactant in Aqueous Solution. Bis(triethylammonium) 1,20-Eicosanediyl Disulfate

Abstract: The physicochemical properties of the α,ω-type (bolaform) surfactant, bis(triethylammonium) 1,20-eicosanediyl disulfate (α,ω C20N2Et6), in aqueous solution have been investigated by means of surface tension, electrical conductivity, dye solubilization and time-resolved fluorescence quenching. The critical micelle concentration of α,ω C20N2Et6 was 1–1.3×10−3 mol dm−3. The micelle ionization degree of the surfactant was larger than a conventional surfactant having the same head group. From surface tension measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It is seen that N is independent of the surfactant concentration up to 0.2 mol din-3, i. e., well above CMC. Thus, as far as the dependence of N on concentration the behavior of C20Et 6 is rather different from that of two other bolaforms: the docosane-l,22-bis(trimethylammonium bromide) [14] and the bis(triethylammonium)-l,20-eicosane disulfate [24] where N increases significantly with C. The packing parameter [25] of C20Et6 is smaller than that of the other two bolaforms, mostly because of difference in surface areas per head group. Recall that the 1H NMR signals of the normal surfactant, cetyltrimethylammonium bromide, is dramatically broadened upon formation of rod-like micelles [23].…”
Section: Aggregation Numbermentioning
confidence: 89%
“…It is seen that N is independent of the surfactant concentration up to 0.2 mol din-3, i. e., well above CMC. Thus, as far as the dependence of N on concentration the behavior of C20Et 6 is rather different from that of two other bolaforms: the docosane-l,22-bis(trimethylammonium bromide) [14] and the bis(triethylammonium)-l,20-eicosane disulfate [24] where N increases significantly with C. The packing parameter [25] of C20Et6 is smaller than that of the other two bolaforms, mostly because of difference in surface areas per head group. Recall that the 1H NMR signals of the normal surfactant, cetyltrimethylammonium bromide, is dramatically broadened upon formation of rod-like micelles [23].…”
Section: Aggregation Numbermentioning
confidence: 89%
“…But, strikingly, CMC values of both bola-surfactants and of gemini-surfactants are lowered by one order of magnitude or more in Examples of "oligomeric" surfactants: a "bola" dimer [426][427][428]; b "gemini" dimer [435,445,448]; c cyclic hexamer of "tail end" type [419]; d star-shaped trimer of "tail end" type [420] comparison to the corresponding "monomers" [239, 424,[428][429][430][431][432][433][434]. The reduction of the surface tension appears slightly lower than for the monomers, but the surface activities are still substantial [330,405,413,424,427,[429][430][431][432][433][434][435]. Interestingly, above the CMC a number of dimeric surfactants do not show the standard plateau of surface tension but exhibit a small but continuous decrease with increasing concentration.…”
Section: Defined Oligomeric Surfactantsmentioning
confidence: 99%
“…From surface tension studies of bola-surfactants, it is concluded that they exhibit wicket-like conformations at the gas-water interface [239, 428,430,431]. In micelles and liquid crystals however, a stretched conformation is preferred [436,437]; this implies that surface tension data and interfacial tension data do no more describe the "micellar" interface with all the implications for solubilization (compare Sect.…”
Section: Defined Oligomeric Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“… Dye 3 OrangeOT/C.I Orange 2 11.5(Ikeda et al, 1989) Dye 4 C.I Red 19 2.7(Choi et al, 2000) Dye 5 Sudan 4/Red 25 2.2 and 2.8(Imae et al, 1986;Abe et al, 1987) …”
mentioning
confidence: 99%